The Effect of the Arrangement to Implement Local Working of Patents on the Policy of State's Responsibility in Fulfilling Public Accessibility Rights to Patent Medicine - Rahayu Rahayu; Kholis Roisah; Diastama Anggita Ramadhan; Leony Sondang Suryani (Badan Strategi Kebijakan Hukum, 2022)
The amendment of Article 20 of Law Number 13 of 2016 concerning Patents through Article 107 of Law Number 11 of 2020 concerning Job Creation raises concern. The public shows concern that their accessibility rights to get medicines in order to fulfill the right to health will be restricted. There is a conflict of interest between Government of Indonesia's obligation to fulfill its citizen's right to access medicine and its commitment to international agreements. This study used a doctrinal approach by analyzing secondary data. Specifically, it analyzed various policies related to the provision of medicines by government as part of it s obligations to fulfill the right to health of its citizens. The results of this study conclude that the state's obligation to fulfill the accessibility of patent medicine is carried out through several policies. These policies include the policy on the development of the pharmaceutical industry for medicine raw materials and innovative medicine. There is also the policies on ensuring the safety and efficacy of medicine through medicine registration. The government also fulfills the accessibility of patent medicine through the policies for medicine availability in urgent circumstances with the implementation of patent held by the government (governmental use). In addition, there is also the policy of independence in the use of domestically produced medicine. The policy on the obligation to apply local patent that can be replaced by importing does not really affect the availability of patent medicine. It is because the technological capabilities of the pharmaceutical industry are still limited to the ability to formulate medicine. Indonesian pharmaceutical industry does not yet have the ability for the development of innovative medicine. Furthermore, the government issues various policies and regulations to facilitate the acceptance of qualified generic medicine. It is done to meet the needs of the community, as well as to fulfill the right to health for the community as part of the state's obligations. Indonesia as a country rich in bio-diversity needs mandatory policies for national pharmaceutical companies to develop raw materials for biopharmaceutical medicine.